EXPRESSIONS OF IGF-1R, EZH2, LAMININ-5 IN LEUKOPLAKIA AND ORAL_x000D_ SQUAMOUS CELL CARCINOMA - NAMDAR PEKİNER, FİLİZ MEDİHA (My University, 2021)
Aim: The aim of this study is to investigate the expressions of IGF-1R, EZH2 and Laminin-5 antibodies in biopsy samples ofleukoplakia and squamous cell carcinoma of the oral mucosa by immunohistochemistry method.Materials and Methods: The study consisted of three groups; oral squamous cell carcinoma leukoplakia and control groups.The control group consisted of lesions with oral fibrous hyperplasia diagnosis. Biopsies of 38 patients for oral squamous cellcarcinoma, 32 patients for leukoplakia and 15 patients for control group were examined and evaluated degree of staining ofantibodies. Antibodies were evaluated as negative (0-10%):0, 1 positive (11-30%):+, 2 positive (31-60%):++, 3 positive (61-100%):+++ according to staining percentages. The staining degrees of antibodies were compared with Mann Whitney U test instudy and control groups. Gender distribution between groups was compared with Chi-Square test and SPSS 21 program wasused for calculations. The results were statistically significancant is p ˂0.05.Results: According to the findings obtained in this study antibodies revealed significantly higher staining in the oral squamouscell carcinoma group and leukoplakia group compared to with control groups.Conclusion: In this study, it was shown that EZH2, IGF-1R and Laminin-5 may have roles in cancer development.

Amaç: Çalışmanın amacı oral mukozada lökoplaki ve skuamöz hücreli karsinom biyopsi örneklerinde IGF-1R, EZH2 ve Laminin5 antikorlarının immünhistokimyasal methodla ekspresyonlarının araştırılmasıdır._x000D_ Gereç ve Yöntem: Çalışmayı oral skuamöz hücreli karsinom, lökoplaki ve kontrol grubu olmak üzere üç grup oluşturmaktadır._x000D_ Kontrol grubunu oral fibröz hiperplazi tanılı lezyonlar oluşturmuştur. Oral skuamöz hücreli karsinomda 38, lökoplakide 32 ve_x000D_ kontrol grubunda 15 biyopsi örneğinde IGF-1R, EZH2 ve Laminin-5 antikorlarının boyanma dereceleri incelendi ve_x000D_ değerlendirildi. Antikorlar boyanma yüzdelerine göre negatif (%0-10):0, 1 pozitif (%11-30):+, 2 pozitif (%31-60):++, 3 pozitif_x000D_ (%61-100):+++ olarak değerlendirildi. Çalışma ve kontrol gruplarında EZH2, IGF-1R ve Laminin-5 antikorları ile boyanma_x000D_ dereceleri Mann Whitney U testiyle karşılaştırılmıştır. Gruplar arasındaki cinsiyet dağılımı karşılaştırılması Ki-kare testiyle,_x000D_ hesaplamalar SPSS 21 programıyla yapılmıştır. Anlamlılık sınırı p˂0.05tir._x000D_ Bulgular: Bu çalışmada elde edilen bulgulara göre IGF-1R, EZH2 ve Laminin-5 antikorlarının kontrol grubuyla karşılaştırıldığında_x000D_ lökoplaki ve oral skuamöz hücreli karsinom gruplarında önemli derecede yüksek boyanma göstermiştir._x000D_ Sonuç: Bu çalışmada EZH2, IGF-1R ve Laminin-5'in kanser gelişiminde rolleri olabileceği gösterilmiştir.
LÖKOPLAKİ VE ORAL SKUAMÖZ HÜCRELİ KARSİNOMDA IGF-1R, EZH2, LAMININ-5 EKSPRESYONU